2018
DOI: 10.1126/sciadv.aat1061
|View full text |Cite
|
Sign up to set email alerts
|

Domain Meissner state and spontaneous vortex-antivortex generation in the ferromagnetic superconductor EuFe 2 (As 0.79 P 0.21 ) 2

Abstract: Adding ferromagnetism to superconductor leads to spatially patterned phases of spontaneously generated vortex-antivortex pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 34 publications
2
39
1
Order By: Relevance
“…Moreover, the bulky character of this transition, only suggested in Ref. [10], is now confirmed by the microwave bulk-sensitive analysis. The low-temperature χ m peak, specific to the high-frequency characterization, corresponds to a transition between different vortex-antivortex dynamical regimes, to a spin reorientation transition of the Eu 2+ canted ferromagnetic subsystem, or to an interplay between the two phenomena.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Moreover, the bulky character of this transition, only suggested in Ref. [10], is now confirmed by the microwave bulk-sensitive analysis. The low-temperature χ m peak, specific to the high-frequency characterization, corresponds to a transition between different vortex-antivortex dynamical regimes, to a spin reorientation transition of the Eu 2+ canted ferromagnetic subsystem, or to an interplay between the two phenomena.…”
Section: Discussionsupporting
confidence: 62%
“…It could also be related to a spin reorientation transition of the Eu 2+ canted ferromagnetic subsystem (spin canting does not give contrast in MFM maps). A spin glass transition should probably be excluded for EuFe 2 (As 1−x P x ) 2 , at least in the investigated doping range, since we observed by MFM a well-defined domain structure, i.e., evidence of long-range ferromagnetic ordering [10].…”
Section: (H)]mentioning
confidence: 72%
See 1 more Smart Citation
“…The sources of flux pinning include random point defects [15], precipitates [16], planar defects [17], and correlated disorder such as twin boundaries [18]. Notwithstanding the coexistence between superconductivity and magnetism usually present in many Fe-SCs [19][20][21], its influence on the resulting vortex dynamics has been little explored.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in phosphorus-doped EuFe2As2, the superconductivity appears below Tc~24K, while at the Curie point, Tm~19K, the Eu-spins order ferromagnetically in layers separated by the superconducting FeAs-sheets and align parallel to the c-axis [10]. Recent MFM studies have found that in this material the Meissner state coexists with very fine ferromagnetic domains that are smaller than the penetration depth and at lower temperatures transforms into a vortex-domain state [11,12].…”
mentioning
confidence: 99%